2015
DOI: 10.1038/srep12279
|View full text |Cite
|
Sign up to set email alerts
|

Independent Emergence of the Cosmopolitan Asian Chikungunya Virus, Philippines 2012

Abstract: Outbreaks involving the Asian genotype Chikungunya virus (CHIKV) caused over one million infections in the Americas recently. The outbreak was preceded by a major nationwide outbreak in the Philippines. We examined the phylogenetic and phylogeographic relationships of representative CHIKV isolates obtained from the 2012 Philippines outbreak with other CHIKV isolates collected globally. Asian CHIKV isolated from the Philippines, China, Micronesia and Caribbean regions were found closely related, herein denoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…E2-L248F was described in 2012 CHIKV strains from the Philippines that are part of the B3 cosmopolitan Asian CHIKV clade derived from a common ancestor dated to 2003. 45 All Philippines CHIKV strains isolated from the nationwide 2012 outbreaks within this clade, as well as other CHIKV isolates from China (2012), Micronesia (2013), and the Caribbean (2013-2014) have E2-248F. On the basis of its proximity to known vector-adaptive substitutions, E2-L248F deserves further study.…”
Section: Resultsmentioning
confidence: 99%
“…E2-L248F was described in 2012 CHIKV strains from the Philippines that are part of the B3 cosmopolitan Asian CHIKV clade derived from a common ancestor dated to 2003. 45 All Philippines CHIKV strains isolated from the nationwide 2012 outbreaks within this clade, as well as other CHIKV isolates from China (2012), Micronesia (2013), and the Caribbean (2013-2014) have E2-248F. On the basis of its proximity to known vector-adaptive substitutions, E2-L248F deserves further study.…”
Section: Resultsmentioning
confidence: 99%
“…However, the 2011–2013 outbreak in the Philippines was caused mainly by the Asian genotype; the reason that this large outbreak was caused by this genotype is unknown. Previous reports have confirmed the reemergence of Asian genotype viruses in the Philippines ( 8 , 9 ). In this study, phylogenetic analysis and Bayes factor calculation showed that the Philippines viruses were closely related to Indonesian viruses, which might explain why the outbreak started in southern Mindanao, near Indonesia.…”
Section: Discussionmentioning
confidence: 55%
“…data). Previous studies of chikungunya fever in the Philippines focused on clinical and serologic analyses ( 7 ), and recent reports on the molecular surveillance of CHIKV in the country were limited and analyzed only samples collected in 2012 ( 8 , 9 ). We conducted genetic analysis to characterize recent CHIKV infections that caused a large nationwide outbreak in the Philippines during 2011–2013.…”
mentioning
confidence: 99%
“…In 2012 and 2013, cases of Chikungunya fever have been confirmed in 43 of the country's 80 provinces and outbreaks have been reported (129).…”
Section: Vectorsmentioning
confidence: 99%
“…In Asia, the first CHIKV epidemic was documented in 1958 in Bangkok, Thailand (45) followed by numerous documented outbreaks in the Philippines, Cambodia, Vietnam, Laos, Myanmar, Malaysia and Indonesia (129).…”
Section: Vectorsmentioning
confidence: 99%